Factors associated with pain severity, pain interference, and perception of functional abilities independent of joint status in US adults with hemophilia: Multivariable analysis of the Pain, Functional Impairment, and Quality of Life (P‐FiQ) study. (2nd March 2018) - Kempton, Christine L.; Buckner, Tyler W.; Fridman, Moshe; Iyer, Neeraj N.; Cooper, David L.
Abstract: Introduction: Levels of pain and dysfunction appear to differ among people with hemophilia despite similar levels of joint disease. Objective: To determine patient characteristics that influence pain and function independent of joint status. Methods: US adults with hemophilia completed a survey that included information on clinical characteristics, demographics, and patient‐reported outcome instruments assessing pain (Brief Pain Inventory v2 Short Form [BPI]), functional impairment (Hemophilia Activities List [HAL]), and health status (EQ‐5D‐5L). Additionally, physiotherapists optionally completed a clinical joint evaluation (Hemophilia Joint Health Score [HJHS]). Associations were examined using simple and multiple regression models. Results: Of 381 adults enrolled, 240 had complete HJHS scores (median age, 32 years). After controlling for HJHS and opiate use, anxiety/anxiolytic use was significantly associated with worse pain severity and interference scores. After controlling for HJHS, the most significant predictors of functional impairment were older age, unemployment, more severe hemophilia, and greater pain. EQ‐5D‐5L pain/discomfort was associated with worse outcomes on most HAL scores. Conclusion: Unemployment, anxiety, and depression were each associated with both greater pain and functional disability after controlling for joint status. Continued attention to pain and psychosocial issues will be important in improving clinical care and research efforts in the hemophilia population.